Outlook of the Communication & Signaling System for Vacuum PipelineUltra High Speed Maglev Train - LIU Zhenyu; YANG Kai; FAN Liang; QU Yongzheng (Kongzhi Yu Xinxi Jishu)
Vacuum pipeline ultra high speed maglev train is a new railway transit technology. Its operation control system can be divided into three levels: centralized control system, zone control system and onboard control system. In this paper, new functions and key points of the onboard and zone control subsystems are proposed. In the aspect of central control system and communication system, the strategy on how to select and improve existing products is analyzed. Finally, application prospects of vacuum pipeline ultra-high-speed maglev train is proposed. With the support of the existing technologies, design and development of its communication & signaling system and the laboratory verification can be carried out.